Enhanced rhizoremediation of polychlorinated biphenyls by resuscitation-promoting factor stimulation linked to plant growth promotion and response of functional microbial populations. (December 2022) - Ren, Hejun; Ding, Yuzhu; Hao, Xinyu; Hao, Jianjun; Liu, Jinliang; Wang, Yan
Abstract: Rhizoremediation is acknowledged as a green technology for removing polychlorinated biphenyls (PCBs) in soil. However, rhizoremediation is limited because most soil microorganisms enter into a viable but non-culturable (VBNC) state under PCBs stress. This work was to study the effect of resuscitation-promoting factor (Rpf) on rhizoremediation efficiency of PCBs in alfalfa and rhizosphere microbiological communities. Results suggested that Rpf promoted alfalfa growth in PCB-contaminated soil by improving antioxidant enzymes and detoxification metabolites in alfalfa. After 40 d Rpf treatment, removal rate for five selected PCBs significantly increased by 0.5–2.2 times. Rpf enhanced relative abundances of bphA and bphC responsible for degrading PCBs, and enzymatic activities of metabolizing exogenous compounds in rhizosphere soil. High-throughput sequencing showed that Rpf did not change the dominant microbial population at phyla and genera levels, but caused variation of the bacterial community structures. The promoting function of Rpf was linked to the shift of various key populations having different functions depending on Rpf concentrations. Pseudomonas and Rhizobium spp. enrichment might stimulate PCB degradation and Streptomyces and Bacillus spp. primarily contributed to alfalfa growth. Predicted functions in rhizosphere soil bacterial community indicated Rpf facilitated soil nutrient cycling and environmental adaptation. This study indicated that Rpf was an active additive for strengthening rhizoremediation efficiency of PCB-contaminated soil and enhancing their in-situ remediation. Graphical abstract: Image 1 Highlights: Rpf enhanced the efficiency of PCBs degradation in rhizosphere soil. Rpf promoted alfalfa growth by increasing PGPB growth and plant metabolism. Rpf modulated various beneficial microbial populations in rhizosphere soil.